Managing Volatility : A Vulnerability Exercise for Low-Income Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This paper, introduces the analytical framework for a Vulnerability Exercise for Low-Income Countries (VE-LIC). The envisaged exercise will strive to identify vulnerabilities and emerging risks that arise from changes in the external environment in a consistent manner across countries and across time. The objective is to strengthen the staff's capacity to spot vulnerabilities and flag potential pressure points in LICs arising from external triggers before they materialize.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet